2018
DOI: 10.1002/jnr.24258
|View full text |Cite
|
Sign up to set email alerts
|

Impact of transcranial direct current stimulation on structural plasticity of the somatosensory system

Abstract: While there is a growing body of evidence regarding the behavioral and neurofunctional changes in response to the longitudinal delivery of transcranial direct current stimulation (tDCS), there is limited evidence regarding its structural effects. Therefore, the present study was intended to investigate the effect of repeatedly applied anodal tDCS over the primary somatosensory cortex on the gray matter (GM) and white matter (WM) compartment of the brain. Structural tDCS effects were, moreover, related to effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 77 publications
(170 reference statements)
1
7
0
Order By: Relevance
“…However, as the control group did not receive any training, the results did not allow conclusions about whether effects were due to tDCS or training or both. Applying anodal tDCS over the left somatosensory cortex during repeated sensory learning, Hirtz and colleagues 61 found FA increases in anodal compared to sham group in the left frontal cortex, in the vicinity of the middle and superior frontal gyrus. The authors concluded that sensory learning involved prefrontal areas rather than stimulation target regions underneath the anodal electrode due to involvement of decision-making processes recruiting the frontoparietal network.…”
Section: Discussionmentioning
confidence: 99%
“…However, as the control group did not receive any training, the results did not allow conclusions about whether effects were due to tDCS or training or both. Applying anodal tDCS over the left somatosensory cortex during repeated sensory learning, Hirtz and colleagues 61 found FA increases in anodal compared to sham group in the left frontal cortex, in the vicinity of the middle and superior frontal gyrus. The authors concluded that sensory learning involved prefrontal areas rather than stimulation target regions underneath the anodal electrode due to involvement of decision-making processes recruiting the frontoparietal network.…”
Section: Discussionmentioning
confidence: 99%
“…Full-text articles were examined in cases of insufficient information in the title or abstract. In total, 73 full-text articles were screened for eligibility and 16 articles were removed for the following reasons: (1) primary outcome not assessed (Gundlach et al, 2017;Hornburger et al, 2019;Huh et al, 2016;Maddaluno et al, 2020;Zapallow et al, 2013); (2) primary outcome measured during rather than before and after NIBS (Manzo et al, 2020;Saito et al, 2021;Yokota et al, 2021); (3) primary outcome measured more than 24 h post-NIBS (Litvak et al, 2007); (4) SEPs measured from the lower limb (Zapallow et al, 2012); (5) NIBS not applied to the S1 (Uguisu et al, 2010); (6) number of participants for a given NIBS condition (dataset) < 5 (Sehm et al, 2013); (7) SEPs evoked by electrical stimulation only on the upper limb side ipsilateral to NIBS; (8) NIBS also administrated with repetitive tactile stimulation to induce S1 plasticity (Ragert et al, 2003); (9) SEP data filtered with a bandpass of 400-800 Hz to analyse high-frequency oscillations (Restuccia et al, 2007); and (10) data previously analysed by Hilgenstock et al (2016) (Hirtz et al, 2018). One additional article was added by the full-text assessment (Gatica Tossi et al, 2013).…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…However, this possibility is difficult to reconcile with evidence showing atDCS-induced structural changes in gray and white matter (Hirtz et al, 2018 ), which suggests that the effects of atDCS can outlast its time of application. Moreover, when learning is considered from a synaptic perspective (Baltaci et al, 2019 ), interventions that are presumed to facilitate synaptic plasticity should translate, at least partly, to enduring synaptic changes.…”
Section: Discussionmentioning
confidence: 96%